Method for preparing Ziegler-Natta catalysts for low density copolymer polymerization

The method of reacting dialkylmagnesium with inorganic chloride to produce a magnesium chloride support and then adding alkylaluminum chloride and titanium compounds simplifies the production of Ziegler-Natta catalysts, reducing impurities and improving the physical properties of low density copolymers.

JP2025513689APending Publication Date: 2025-04-30SK INNOVATION CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024552053
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-20
Filing Date
2023-04-20
Publication Date
2025-04-30

AI Technical Summary

Technical Problem

Existing methods for producing Ziegler-Natta catalysts are complex and prone to impurity formation, making them challenging for mass production and resulting in polymers with non-uniform distribution.

Method used

A method involving the reaction of dialkylmagnesium with an inorganic chloride to produce a magnesium chloride support, followed by the sequential addition of alkylaluminum chloride and titanium compounds, to create a Ziegler-Natta catalyst with δ-type crystalline properties.

Benefits of technology

This method simplifies the catalyst production process, reduces impurity formation, and enables the production of low density copolymers with improved physical properties, such as increased acquisition rate and catalyst mileage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025513689000001_ABST
    Figure 2025513689000001_ABST
Patent Text Reader

Abstract

The present disclosure relates to a method for preparing a Ziegler-Natta catalyst for low density copolymer polymerization, specifically, a method for preparing a magnesium chloride support using an inorganic chloride as a halogen source for the magnesium chloride support. In one embodiment, the method for preparing a Ziegler-Natta catalyst uses an inorganic chloride in the preparation of the magnesium chloride support, which simplifies the reaction conditions and minimizes the generation of impurities, facilitating mass production.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for making a Ziegler-Natta catalyst for the polymerization of low density copolymers. [Background technology]

[0002] Ziegler-Natta (Z / N) type polymerization catalysts are catalysts for producing olefin polymers, such as ethylene copolymers. Typically, Ziegler-Natta catalysts contain magnesium compounds, aluminum compounds, and titanium compounds supported on a specific support.

[0003] The shape and size of polymers polymerized using Ziegler-Natta catalysis are determined by the catalyst used, so it is important to produce catalysts that can increase productivity and produce polymers with uniform distribution.

[0004] Various development efforts have been made to manufacture Ziegler-Natta catalysts, but some methods are quite sensitive to manufacturing conditions or produce large amounts of impurities or waste, making it difficult to mass-produce the catalyst. US Patent No. 8,003,741 describes a manufacturing method in which a magnesium compound is dissolved in alcohol and then a titanium compound is added, but this has the disadvantages of being complicated in the manufacturing process and using many types of materials. Summary of the Invention [Problem to be solved by the invention]

[0005] One embodiment provides a method for making a Ziegler-Natta catalyst for the polymerization of low density copolymers.

[0006] Another embodiment provides a method for producing a low density copolymer comprising contacting an olefin monomer with a Ziegler-Natta catalyst for polymerizing a low density copolymer according to an embodiment. [Means for solving the problem]

[0007] One embodiment of the present invention includes the steps of reacting a dialkyl magnesium with an inorganic chloride represented by the following chemical formula 1 to obtain a magnesium chloride support; and adding an alkylaluminum chloride represented by the following chemical formula 2 and a metal compound containing titanium (Ti) to the magnesium chloride support in that order, and reacting the aluminum chloride with the magnesium chloride support. [Chemical formula 1] R 1 x AlCl 3-x In the above Chemical Formula 1, R 1 are each independently 1-10 Alkyl or C 3-10 is cycloalkyl, x is an integer from 0 to 2. [Chemical formula 2] R 2 y AlCl 3-y In the above Chemical Formula 2, R 2 are each independently 1-10 Alkyl or C 3-10 is cycloalkyl, y is 1 to 2.

[0008] Another embodiment provides a method for producing a magnesium chloride support having δ-phase crystallinity, which has a peak at the following diffraction angle 2θ in an X-ray diffraction pattern, comprising a step of reacting a dialkylmagnesium with an inorganic chloride represented by the following chemical formula 1: 15.0°±3.0°, 30.0°±3.0°, 50.0°±3.0°; [Chemical formula 1] R 1 x AlCl 3-x In the above Chemical Formula 1, R 1 are each independently 1-10 Alkyl or C 3-10 is cycloalkyl, x is an integer from 0 to 2.

[0009] Another embodiment provides a process for producing a low density copolymer comprising the step of contacting an olefin monomer with a Ziegler-Natta catalyst for polymerizing low density copolymers according to one of the above embodiments. Effect of the Invention

[0010] The present disclosure relates to a method for preparing a Ziegler-Natta catalyst for low density copolymer polymerization, specifically, a method for preparing a magnesium chloride support using an inorganic chloride as a halogen source for the magnesium chloride support. In one embodiment, the method for preparing a Ziegler-Natta catalyst uses an inorganic chloride in the preparation of the magnesium chloride support, which simplifies the reaction conditions and minimizes the generation of impurities, facilitating mass production. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 shows XRD data of (a): existing α-type (δ-phase) MgCl2, (b): existing δ-type (δ-phase) MgCl2, and (c) MgCl2 produced in Example 1. [Diagram 2] FIG. 1 shows the results of analysis of a polymer produced using the Ziegler-Natta catalyst produced in an example by crystallization elution fractionation (CEF). [Diagram 3] FIG. 1 shows the results of analysis of a polymer produced using a Ziegler-Natta catalyst produced in a comparative example by crystallization elution fractionation (CEF). [Figure 4] FIG. 1 shows the results of analysis of a polymer produced using a Ziegler-Natta catalyst produced in a comparative example by crystallization elution fractionation (CEF). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The embodiments described in this specification can be modified into various other forms, and the technology according to one embodiment is not limited to the embodiment described below. In addition, the embodiment of one embodiment is provided to more completely explain the present invention to those having average knowledge in the art. Furthermore, throughout the specification, "including" a certain component does not mean excluding other components, but may further include other components, unless otherwise specified to the contrary.

[0013] Numerical ranges used in this specification include lower and upper limits, all values ​​within the range, increments logically derived from the form and width of the range defined, and all values ​​limited therein, and all possible combinations of upper and lower limits of the numerical ranges limited in different forms. As an example, if the content of a composition is limited to 10% to 80% or 20% to 50%, it should be interpreted that the numerical ranges of 10% to 50% or 50% to 80% are also described in this specification. Unless otherwise specified in this specification, values ​​outside the numerical range that may occur due to experimental error or rounding of values ​​are also included in the defined numerical range.

[0014] Hereinafter, unless otherwise defined, "about" is understood to mean a value within 30%, 25%, 20%, 15%, 10% or 5% of the specified value.

[0015] Hereinafter, in this specification, "alkyl" is defined as meaning either alkyl or cycloalkyl, and even if there is no specific definition, alkyl or cycloalkyl can be interpreted as including derivatives that can be easily modified by a person skilled in the art to the extent that a similar effect is expected to be exerted, or those substituted with conventional substituents (e.g., halogen, etc.).

[0016] One embodiment provides a method for preparing a Ziegler-Natta catalyst for the polymerization of low density copolymers, which provides facile reaction conditions and minimizes the production of impurities.

[0017] Specifically, the method for producing the Ziegler-Natta catalyst includes the steps of reacting dialkyl magnesium with an inorganic chloride represented by the following chemical formula 1 to obtain a magnesium chloride support; and adding an alkylaluminum chloride represented by the following chemical formula 2 and a metal compound containing titanium (Ti) to the magnesium chloride support in that order, and reacting them.

[0018] [Chemical formula 1] R 1 x AlCl 3-x

[0019] In the above Chemical Formula 1, R 1 are each independently 1-10 Alkyl or C 3-10 is cycloalkyl, x is 0 to 2.

[0020] [Chemical formula 2] R 2 y AlCl 3-y

[0021] In the above Chemical Formula 2, R 2 are each independently 1-10 Alkyl or C 3-10 is cycloalkyl, y is 1 to 2.

[0022] According to an embodiment of the present invention, a magnesium chloride support containing high purity δ-type magnesium chloride can be produced by using an inorganic chloride as a halogen source for the support when producing the magnesium chloride support. In addition, when a low-density copolymer is polymerized using the Ziegler-Natta catalyst produced by the above-mentioned production method, the low-density copolymer can be produced with a significantly increased yield (amount) and / or catalyst mileage, and since the catalyst has excellent comonomer reactivity, the copolymer has excellent properties such as a high ratio of low-density regions and a high elongation rate compared to copolymers produced using Ziegler-Natta catalysts produced using organic chlorides and / or commercial low-density copolymers.

[0023] Meanwhile, when organic chlorides (R-Cl (e.g., t-BuCl, t-amylCl), H-Cl, etc.) are used as halogen sources for the support as in the conventional method, the organic chlorides contain impurities, which not only make it difficult to produce a high-purity magnesium chloride support, but also may have a detrimental effect on catalytic activity, and the reactivity of organic chlorides with dialkyl magnesium is low, requiring a step of heating at a high temperature during the reaction, making the reaction difficult. In particular, when producing magnesium chloride supports using hydrogen chloride (HCl) gas, hydrogen chloride gas, a highly dangerous and toxic compound, is used, which requires the use of corrosion-resistant special equipment and permission for handling the compound, making it difficult to mass-produce the catalyst.

[0024] In one embodiment, the metal compound may further include a transition metal, for example, a group IV or V metal. Specifically, the metal compound may further include one or more metals selected from the group consisting of Zr, Hf, V, Nb, and Ta. Here, the metal may be included in the form of a chloride, an alkoxy chloride, an alkylate, etc., but this is merely an example and is not necessarily limited thereto.

[0025] In one embodiment, the titanium (Ti)-containing metal compound is TiX4 or (R 3 O)z Ti(X) 4-z wherein X is a halogen atom selected from I, Br, Cl, and F; 3 are each independently a straight or branched chain C 1-10 Alkyl, C 1-8 Alkyl, C 2-6 Alkyl or C 1-5 alkyl, and z is an integer of 1 to 4. Specific examples of the metal compound include TiCl4, TiBr4, TiI4, Ti(OBu)4, Ti(Oi-Pr)4, Ti(OEt)4, Ti(OEt)2(Cl)2, and Ti(OEt)(Cl)3. However, this is merely an example and is not necessarily limited thereto.

[0026] In one embodiment, R 1 are each independently a straight or branched chain C 1-6 Alkyl, C 1-5 Alkyl, C 2-5 Alkyl, -CH3, -CH2CH3, -CH2CH2CH3, -CH2CH2CH2CH3, C 3-6 Cycloalkyl, C 4-6 Cycloalkyl or C 5-6 It may be cycloalkyl, but this is by way of example only and is not necessarily limited thereto.

[0027] In one embodiment, the x may be 0 to 2, or 1 to 2, and specifically may be 0, ½, 1, 3 / 2, or 2.

[0028] The inorganic chloride represented by Formula 1 may be used as a halogen source for the magnesium chloride support. In one embodiment, the inorganic chloride is EtAlCl2 (ethyl aluminium dichloride), MeAlCl2 (methyl aluminium dichloride), PrAlCl2 (propyl aluminium dichloride), BuAlCl2 (butyl aluminium dichloride), or CH 15 Al2Cl3 (i.e., (C2H5) 3 / 2 AlCl 3 / 2 ) (Ethyl aluminium sesquichloride), and one or more of them may be used simultaneously or in combination. In one embodiment, the inorganic chloride may be an alkylaluminum monomer or dimer.

[0029] R 2 are each independently a straight or branched chain C 1-6 Alkyl, C 1-5 Alkyl, C 2-5 Alkyl, -CH3, -CH2CH3, -CH2CH2CH3, -CH2CH2CH2CH3, C 3-6 Cycloalkyl, C 4-6 Cycloalkyl or C 5-6 It may be cycloalkyl, but this is by way of example only and is not necessarily limited thereto.

[0030] In one embodiment, the y may be 1 to 2, and specifically, may be 1, 3 / 2, or 2.

[0031] In one embodiment, the alkylaluminum chloride represented by Formula 2 is CH 15 Al2Cl3 (i.e., (C2H5) 3 / 2 AlCl 3 / 2) (Ethyl aluminium sesquichloride), EtAlCl2 (Ethyl aluminium dichloride), MeAlCl2 (Methyl aluminium dichloride), PrAlCl2 (Propyl aluminium dichloride), or BuAlCl2 (Butyl aluminium dichloride), and one or more may be used simultaneously or in combination. In one embodiment, the alkylaluminium chloride may be a monomer or a dimer.

[0032] In one embodiment, the dialkylmagnesium is a linear or branched C 1-10 Alkyl or C 3-10 Each cycloalkyl may be independently substituted. 1-6 Alkyl, C 1-5 Alkyl, C 2-5 Alkyl, -CH3, -CH2CH3, -CH2CH2CH3, -CH2CH2CH2CH3, C 3-6 Cycloalkyl, C 4-6 Cycloalkyl or C 5-6 Two substituents independently selected from cycloalkyl may be substituted. In one embodiment, the dialkyl magnesium may be Et(n-Bu)Mg (ethyl normal butyl magnesium).

[0033] In one embodiment, the magnesium chloride support may contain δ-phase crystallinity. For example, the magnesium chloride support may mainly contain δ-phase crystallinity, and the δ-phase crystallinity may be 90% or more, 80% or more, 70% or more, 60% or more, or 50% or more. In one embodiment, the magnesium chloride support may be high-purity magnesium chloride mainly containing δ-phase crystallinity.

[0034] In one embodiment, the δ-form magnesium chloride may have peaks at the following diffraction angles 2θ in an X-ray diffraction (XRD) pattern:

[0035] 15.0°±3.0°, 30.0°±3.0°, 50.0°±3.0°.

[0036] The δ-form magnesium chloride according to the embodiment may have a broad peak in the range of the peak value. Alternatively, the 2θ value may be, for example, 15.0°±2.0°, 32.0°±2.0°, 50.0°±2.0°; or 15.0°±1.0°, 32.0°±1.0°, 50.0°±1.0°. The diffraction angle value may include an error value within a range of about ±0.2°.

[0037] In one embodiment, the metal compound and the alkylaluminum chloride represented by Chemical Formula 2 may be added in a molar ratio of 1:2 to 1:10, 1:2 to 1:8, 1:3 to 1:8, 1:3 to 1:7, or 1:3.5 to 1:7, although this is merely an example and is not necessarily limited thereto.

[0038] In one embodiment, the metal compound and the magnesium chloride support may be reacted in a molar ratio of 1:0.1 to 1:30, 1:5 to 1:30, 1:8 to 1:25, 1:10 to 1:25, 1:11 to 1:22, or 1:12 to 1:21, although this is merely an example and is not necessarily limited thereto.

[0039] In one embodiment, the molar ratio of the dialkyl magnesium to the inorganic chloride represented by Chemical Formula 1 may be 1:1 to 1:4, 1:1 to 1:3.5, 1:1.1 to 1:3, 1:1.5 to 1:3, 1:1.1 to 1:2.5, or 1:1.5 to 1:2.5, but this is merely an example and is not necessarily limited thereto.

[0040] In one embodiment, the inorganic chloride represented by Chemical Formula 1 and the alkylaluminum chloride represented by Chemical Formula 2 may be, for example, the same compound. In one embodiment, by using the inorganic chloride and the alkylaluminum chloride as the same compound, the economy and efficiency of the production process can be improved. Alternatively, when a low-density copolymer polymerization reaction is carried out using a Ziegler-Natta catalyst produced using the same inorganic chloride and alkylaluminum chloride, the amount of polymer obtained and the low-density region contained in the polymer can be increased, thereby improving the physical properties of the polymer.

[0041] In one embodiment, the step of obtaining the magnesium chloride support may include a step of slowly adding an inorganic chloride dropwise to a magnesium chloride solution at room temperature (e.g., about 5°C to 25°C, about 10°C to 25°C, about 15°C to 25°C, about 18°C ​​to 23°C) to produce a magnesium chloride slurry.

[0042] In one embodiment, the step of obtaining the magnesium chloride support may be a step of washing (the magnesium chloride slurry solution) with a saturated hydrocarbon solution and then drying to obtain the magnesium chloride support, or a step of diluting (the magnesium chloride slurry solution) with a saturated hydrocarbon solution, removing the supernatant liquid, and drying the solid to obtain the magnesium chloride support.

[0043] In one embodiment, the step of adding an alkylaluminum chloride to the magnesium chloride support may include a step of diluting the obtained high purity solid magnesium chloride in a saturated hydrocarbon (e.g., heptane) solution to produce a slurry, and then adding the alkylaluminum chloride diluted in a saturated hydrocarbon (e.g., hexane) solution at room temperature (e.g., about 5°C to 25°C, about 10°C to 25°C, about 15°C to 25°C, about 18°C ​​to 23°C).

[0044] In one embodiment, the support produced by the method for producing a Ziegler-Natta catalyst for polymerization of low density copolymers may have a particle size of about 5 nm or less based on XRD analysis (support (MgCl2) peak at 2θ=50°), or may be, for example, 2 nm to 5 nm, 2.5 nm to 5 nm, or 3 nm to 5 nm.

[0045] Another embodiment provides a method for preparing a magnesium chloride support using an inorganic chloride, which is a step in a method for preparing a Ziegler-Natta catalyst for polymerization of low density copolymers according to an embodiment.

[0046] Specifically, one embodiment provides a method for producing a magnesium chloride support containing δ-phase crystallinity having a peak at the following diffraction angle 2θ in an X-ray diffraction pattern, the method comprising the step of reacting a dialkyl magnesium with an inorganic chloride represented by the following chemical formula 1:

[0047] 15.0°±3.0°, 30.0°±3.0°, 50.0°±3.0°;

[0048] [Chemical formula 1] R 1 x AlCl 3-x

[0049] In the above Chemical Formula 1, R 1 are each independently 1-10 Alkyl or C 3-10 is cycloalkyl, x is 0 to 2.

[0050] According to an embodiment of the present invention, a magnesium chloride support containing high purity δ-type magnesium chloride can be produced by using an inorganic chloride as a halogen source for the support when producing the magnesium chloride support. In addition, when a low-density copolymer is polymerized using the Ziegler-Natta catalyst produced by the above-mentioned production method, the low-density copolymer can be produced with a significantly increased yield (amount) and / or catalyst mileage, and has excellent physical properties such as a high ratio of low-density regions and a high elongation rate compared to copolymers produced using Ziegler-Natta catalysts produced using organic chlorides and / or commercial low-density copolymers.

[0051] In one embodiment, R 1 are each independently a straight or branched chain C 1-6 Alkyl, C 1-5 Alkyl, C 2-5 Alkyl, -CH3, -CH2CH3, -CH2CH2CH3, -CH2CH2CH2CH3, C 3-6 Cycloalkyl, C 4-6 Cycloalkyl or C 5-6 It may be cycloalkyl, but this is by way of example only and is not necessarily limited thereto.

[0052] In one embodiment, the x may be 0 to 2, or 1 to 2, and specifically may be 0, ½, 1, 3 / 2, or 2.

[0053] The inorganic chloride represented by Formula 1 may be used as a halogen source for the magnesium chloride support. In one embodiment, the inorganic chloride is EtAlCl2 (ethyl aluminum dichloride), MeAlCl2 (methyl aluminum dichloride), PrAlCl2 (propyl aluminum dichloride), BuAlCl2 (butyl aluminum dichloride), or CH 15 Al2Cl3 (i.e., (C2H5) 3 / 2 AlCl 3 / 2 ) (Ethyl aluminium sesquichloride), and one or more of them may be used simultaneously or in combination. In one embodiment, the inorganic chloride may be an alkylaluminum monomer or dimer.

[0054] In one embodiment, the magnesium chloride support may include δ-phase crystallinity. For example, the magnesium chloride support may mainly include δ-phase crystallinity, and the δ-phase crystallinity may be 90% or more, 80% or more, 70% or more, 60% or more, or 50% or more. In one embodiment, the magnesium chloride support may be high-purity magnesium chloride mainly including δ-phase crystallinity.

[0055] In one embodiment, the δ-form magnesium chloride may have peaks at the following diffraction angles 2θ in an X-ray diffraction (XRD) pattern:

[0056] 15.0°±3.0°, 30.0°±3.0°, 50.0°±3.0°

[0057] The δ-form magnesium chloride according to the embodiment may have a broad peak in the range of the peak value. Alternatively, the 2θ value may be, for example, 15.0°±2.0°, 32.0°±2.0°, 50.0°±2.0°; or 15.0°±1.0°, 32.0°±1.0°, 50.0°±1.0°. The diffraction angle value may include an error value within a range of about ±0.2°.

[0058] Another embodiment provides a method for producing a low density copolymer using the Ziegler-Natta catalyst for polymerizing low density copolymers according to an embodiment. Specifically, a method for producing a low density copolymer is provided, comprising contacting an olefin monomer with the Ziegler-Natta catalyst for polymerizing low density copolymers according to an embodiment.

[0059] In one embodiment, the olefin monomer may be, for example, an olefin monomer having 2 to 20, 2 to 15, or 4 to 10 carbon atoms.

[0060] In one embodiment, the low density copolymer may be, for example, a linear low density copolymer, and one example may be linear low density polyethylene.

[0061] In one embodiment, the low density copolymer may have a density of 0.91 g / mL to 0.94 g / mL, 0.912 g / mL to 0.938 g / mL, 0.915 g / mL to 0.935 g / mL, or 0.915 g / mL to 0.924 g / mL, but this is by way of example only and is not necessarily limited thereto. In one embodiment, the low density copolymer may have a melt index (MI) measured at about 190° C. according to ISO 1133:1997 or ASTM D1238:1999 of 0.5 g / 10 min to 5.0 g / 10 min, 0.5 g / 10 min to 4.0 g / 10 min, 0.5 g / 10 min to 3.0 g / 10 min, 0.5 g / 10 min to 2.5 g / 10 min, 0.8 g / 10 min to 2.5 g / 10 min, or 1.0 g / 10 min to 2.5 g / 10 min, but this is by way of example only and is not necessarily limited thereto.

[0062] The present invention will be described below by way of specific examples and experimental examples. However, the examples and experimental examples described below are merely illustrative of a portion of the present invention, and the present invention is not limited thereto.

[0063] <Example 1> 33mL (30mmol) of 0.9M ethyl normal butyl magnesium heptane solution was added to a 500mL flask, followed by 90mL of normal heptane. Then, 60mL (60mmol) of 1.0M EtAlCl2 solution was gradually added dropwise at room temperature as the support chloride raw material and stirred for 30 minutes to produce a 0.2M magnesium chloride heptane slurry solution. Next, to remove the residual EtAlCl2, the magnesium chloride slurry was filtered with a filter, washed twice with 50mL of heptane, and then dried to recover the high-purity magnesium chloride support.

[0064] 0.199 g (2.10 mmol) of the recovered high-purity magnesium chloride was used with heptane to prepare a 0.2 M slurry solution, and 10 mL (2.00 mmol) was transferred to a transparent vial and used as an alkylaluminum chloride in a 1.0 M CH15 0.50mL (0.50mmol) of Al2Cl3 solution was added and stirred at room temperature for more than 6 hours. Then, 1.1mL (0.14mmol) of 5wt% TiCl4 as a metal compound was gradually added dropwise and stirred for more than 12 hours to produce a heptane slurry solution containing a brown magnesium chloride supported catalyst (Ziegler-Natta catalyst).

[0065] <Examples 2 to 8> The same method as in Example 1 was carried out, but alkylaluminum chloride and metal compounds were used as shown in Table 1 below to prepare a brown heptane slurry solution containing magnesium chloride supported catalyst (Ziegler-Natta catalyst).

[0066] <Comparative Example 1> 33mL (30mmol) of 0.9M ethyl normal butyl magnesium heptane solution was added to a 500mL flask, followed by 112mL of normal heptane and stirring using a magnetic stirrer. Next, 5.2mL (6.2g, 66mmol) of t-BuCl was gradually added dropwise as a support chloride raw material for 5 minutes while stirring. After that, the internal temperature of the reactor was raised to 50℃-60℃ and the reaction was carried out for more than 2 hours to produce a heptane slurry solution of magnesium chloride support with a concentration of 0.2M.

[0067] Next, 9.3 mL (1.86 mmol) of the prepared 0.2 M magnesium chloride support solution was transferred to a transparent vial and diluted with 1.0 M CH 15 0.50 mL (0.50 mmol) of Al2Cl3 solution was added and stirred at room temperature for more than 6 hours. Then, 1.1 mL (0.14 mmol) of 5 wt% TiCl4 was gradually added dropwise and stirred for more than 12 hours to produce a gray-brown heptane slurry solution of magnesium chloride supported catalyst (Ziegler-Natta catalyst).

[0068] <Comparative Example 2> The same method as in Comparative Example 1 was used, but metal compounds were used as shown in Table 1 below to prepare a gray-brown heptane slurry solution of magnesium chloride supported catalyst (Ziegler-Natta catalyst).

[0069] <Comparative Example 3> 33mL (30mmol) of 0.9M ethyl normal butyl magnesium heptane solution was added to a 500mL flask, followed by 127mL of normal heptane. Before hydrogen chloride (HCl) gas was added, the internal temperature of the reactor was lowered to 0°C and the mixture was stirred using a magnetic stirrer. Anhydrous hydrogen chloride gas was added at a predetermined rate until no residual alkyl magnesium Grignard was observed, and the reaction was terminated to produce a 0.2M concentration heptane slurry solution of magnesium chloride support.

[0070] Next, 9.3 mL (1.86 mmol) of the prepared 0.2 M magnesium chloride support solution was transferred to a transparent vial and diluted with 1.0 M CH 15 0.50 mL (0.50 mmol) of Al2Cl3 solution was added and stirred at room temperature for more than 6 hours. Then, 1.1 mL (0.14 mmol) of 5 wt% TiCl4 was gradually added dropwise and stirred for more than 12 hours to produce a brown heptane slurry solution of magnesium chloride supported catalyst (Ziegler-Natta catalyst).

[0071] <Comparative Examples 4 and 5> The same method as in Comparative Example 3 was used, but alkylaluminum chloride and metal compounds were used as shown in Table 1 below to prepare a brown heptane slurry solution of magnesium chloride supported catalyst (Ziegler-Natta catalyst).

[0072] [Table 1] 1) Alkyl aluminum chloride A: C6H 15Al2Cl3 (Ethyl aluminium sesquichloride); B: C2H5AlCl2 (Ethyl aluminium dichloride) 2) Metal compounds C:TiCl4;D:Ti(Oi-Pr)4;E:TiCl4+VOCl3

[0073] <Experimental Example 1> X-ray diffraction (XRD) analysis The XRD analysis was carried out under the following equipment and analysis conditions to obtain the XRD spectrum of the magnesium chloride support prepared in Example 1.

[0074] Maker: PANalytical; Anode material: Cu; K-Alpha1 wavelength: 1.540598; Generator voltage: 40 kV; Tube current: 30 mA; Scan Range: 20 to 60; Scan Step Size: 0.026; Divergence slit: 1 / 4°; Antiscatter slit: 1 / 2°; Time per step: 100s

[0075] As a result, referring to FIG. 1, (a) is the existing alpha (α) type MgCl, (b) is the existing delta (δ) type MgCl, and (c) is the delta (δ) type MgCl prepared in Example 1. Broad peaks were observed at diffraction angles (2θ) of approximately 15°, 30°, and 50°.

[0076] <Experimental Example 2> Low density copolymer polymerization The autoclave reactor was filled with 0.5 L of saturated hydrocarbon solvent under stable anhydrous nitrogen conditions, and 0.2 g (0.15 mol) of triethylaluminum and 100 mL (70 g, 0.7 mol) of 1-octene were added. The temperature of the reactor was raised to 180°C and stirred, and then ethylene was added to the inside of the reactor at 30 bar. The catalyst (1.7 μmol) in the form of a slurry solution prepared in Examples 1 to 8 and Comparative Examples 1 to 8 was diluted with a saturated hydrocarbon solvent (methylcyclohexane) (3 mL), and the catalyst (1.7 μmol) diluted with the saturated hydrocarbon solvent (3 mL) was transferred to the catalyst port, and the catalyst port was pressurized with anhydrous nitrogen (50 bar). After the autoclave reactor was saturated with ethylene, the catalyst in the catalyst port was added to the inside of the reactor under isothermal conditions at 180°C, and semi-batch polymerization was carried out for 10 minutes while continuing to supply ethylene. Thereafter, the reactants were collected through the discharge port, and the solvent was dried to obtain a low-density copolymer (low-density polyethylene, LLDPE). The amount, catalyst mileage, melting index, and density of the obtained low-density copolymer were measured and shown in Table 2 below.

[0077] Here, the catalyst mileage was defined as the mass of the produced LLDPE divided by the mass of the catalyst. The melt index was measured by testing at 190°C according to the ASTM D1238 standard, and the density was measured by a density measuring device (Density Gradient column).

[0078] [Table 2]

[0079] Referring to Table 2, it can be seen that the yield of copolymer is significantly increased when polymerization is performed using the catalysts prepared in the Examples, compared to when polymerization is performed using the catalysts for low-density copolymer polymerization prepared in the Comparative Examples.

[0080] <Experimental Example 3> Crystallization elution fractionation (CEF) In order to analyze the physical properties of the polymers produced using the catalysts of the Examples and Comparative Examples by crystallization elution fractionation (CEF), a test was performed using a TCB (trichlorobenzene) solution using a POLYMER-CHAR CRYTEX-42 device. In this case, a commercial product A (manufactured by Dow) and a commercial product B (manufactured by SK) were prepared and used as comparative groups. The results are shown in Figures 2 to 4.

[0081] From the above experiment, it was confirmed from the CEF spectrum that the polymer produced using the catalyst of the embodiment has a lower ratio of high density region (homopolymer) at about 90° C. to 100° C. and a higher ratio of low density region (copolymer) at about 50° C. to 90° C. compared to the conventional product. Therefore, it can be seen that the catalyst of the embodiment can be used to effectively produce a low density copolymer with a high elongation ratio.

[0082] Although the present invention has been described in detail above with reference to preferred embodiments and experimental examples, the scope of the present invention is not limited to the specific embodiments, but should be interpreted by the appended claims. In addition, it should be understood that those skilled in the art can make various modifications and variations without departing from the scope of the present invention.

Claims

1. A step of reacting dialkyl magnesium with an inorganic chloride represented by the following chemical formula 1 to obtain a magnesium chloride support; and adding an alkylaluminum chloride represented by the following chemical formula 2 and a metal compound containing titanium (Ti) to the magnesium chloride support in that order, and reacting them. [Chemical formula 1] R 1 x AlCl 3-x In the above Chemical Formula 1, R 1 are each independently 1-10 Alkyl or C 3-10 is cycloalkyl, x is 0 to 2. [Chemical formula 2] In the above Chemical Formula 2, R 2 are each independently 1-10 Alkyl or C 3-10 is cycloalkyl, y is 1 to 2.

2. 2. The method for producing a Ziegler-Natta catalyst for low density copolymer polymerization according to claim 1, wherein the metal compound further comprises a Group IV or Group V metal.

3. 2. The method for producing a Ziegler-Natta catalyst for low density copolymer polymerization according to claim 1, wherein the metal compound further comprises one or more metals selected from the group consisting of Zr, Hf, V, Nb and Ta.

4. The R 1 are each independently 1-6 Alkyl or C 3-6 is cycloalkyl, 2. The method for producing a Ziegler-Natta catalyst for low density copolymer polymerization according to claim 1, wherein x is 1 to 2.

5. The R 2 are each independently 1-6 Alkyl or C 3-6 is cycloalkyl, 2. The method for producing a Ziegler-Natta catalyst for polymerizing low density copolymers according to claim 1, wherein y is 1 to 2.

6. The method for producing a Ziegler-Natta catalyst for polymerization of low-density copolymers according to claim 1, wherein the magnesium chloride support contains δ-phase crystallinity having a peak at the following diffraction angle 2θ in an X-ray diffraction pattern. 15.0゜±3.0゜、30.0゜±3.0゜、50.0゜±3.0゜

7. The method for preparing a Ziegler-Natta catalyst for low-density copolymer polymerization according to claim 1, wherein the metal compound and the alkylaluminum chloride represented by Chemical Formula 2 are added in a molar ratio of 1:2 to 1:

10.

8. The method for preparing a Ziegler-Natta catalyst for polymerization of low density copolymers according to claim 1, wherein the metal compound and the magnesium chloride support are reacted in a molar ratio of 1:0.1 to 1:

30.

9. 2. The method for preparing a Ziegler-Natta catalyst for polymerization of low-density copolymers according to claim 1, wherein the inorganic chloride represented by Chemical Formula 1 and the alkylaluminum chloride represented by Chemical Formula 2 are the same compound.

10. The metal compound is TiX 4 Or (R 3 O) z Ti(X) 4-z Including, Here, X is a halogen atom, and R 3 are each independently 1-10 2. The method for producing a Ziegler-Natta catalyst for polymerizing low density copolymers according to claim 1, wherein z is an alkyl group and z is an integer of 1 to 4.

11. The inorganic chloride represented by the formula 1 and the alkylaluminum chloride represented by the formula 2 are each independently EtAlCl 2 , MeAlCl 2 , PrAlCl 2 , BuAlCl 2 Or (C 2 H 5 ) 3/2 AlCl 3/2 2. The method for producing the Ziegler-Natta catalyst for low density copolymer polymerization according to claim 1,

12. A method for producing a magnesium chloride support comprising a δ-phase crystallinity having a peak at the following diffraction angle 2θ in an X-ray diffraction pattern, the method comprising the step of reacting a dialkylmagnesium with an inorganic chloride represented by the following chemical formula 1: 15.0゜±3.0゜、30.0゜±3.0゜、50.0゜±3.0゜ [Chemical formula 1] R 1 x AlCl 3-x In the above Chemical Formula 1, R 1 are each independently 1-10 Alkyl or C 3-10 is cycloalkyl, x is 0 to 2.

13. 12. A method for producing a low density copolymer, comprising the step of contacting an olefin monomer with a Ziegler-Natta catalyst for polymerizing a low density copolymer, the Ziegler-Natta catalyst being produced by the process according to any one of claims 1 to 11.

14. The low-density copolymer has a density of 0.91 g / mL to 0.94 g / mL and a melt index (MI) measured in accordance with ASTM D1238 of 0.5 g / 10 min to 5.0 g / 10 min. The method for producing a low-density copolymer according to claim 13.